A Novel Approach to the Design of Oversampling Low-Delay Complex-Modulated Filter Bank Pairs. (28th October 2009) - Kurbiel Kurbiel, Thomas Thomas; Göckler Göckler, Heinz G. Heinz G.; Alfsmann Alfsmann, Daniel Daniel
Abstract : In this contribution we present a method to design prototype filters of oversampling uniform complex-modulated FIR filter bank pairs. Especially, we present a noniterative two-step procedure: (i) design of analysis prototype filter with minimum group delay and approximately linear-phase frequency response in the passband and the transition band and (ii) Design of synthesis prototype filter such that the filter bank pairs distortion function approximates a linear-phase allpass function. Both aliasing and imaging are controlled by introducing sophisticated stopband constraints in both steps. Moreover, we investigate the delay properties of oversampling uniform complex-modulated FIR filter bank pairs in order to achieve the lowest possible filter bank delay. An illustrative design example demonstrates the potential of the design approach.